Inhibition of return in time-lapse: Brain Rhythms during grip force control for spatial attention. (10th December 2021) - Zappasodi, Filippo; Croce, Pierpaolo; Di Matteo, Rosalia; Brunetti, Marcella
Abstract: The inhibition of return (IoR) is the observable slowed response to a target at a cued position for cue-target intervals of longer than 300 ms; when there has been enough time to disengage from a previously-cued location, an inhibitory after-effect can be observed. Studies aimed at understanding whether mechanisms underlying IoR act at a perceptual/attentional or a later response-execution stage have offered divergent results. Though focusing on the brain's responses to cue-target intervals can offer significant information on the nature of IoR, few studies have investigated neural activity during this interval; these studies suggest the generation of inhibitory tags on the spatial coordinates of the previously attended position which, in turn, inhibit motor programming toward that position. As such, a cue-target task was administered in this study; the rhythmic activity of EEG signals on the entire cue-target interval was measured to determine whether IoR is referred to early or late response processing stages. A visually-guided force variation during isometric contraction, instead of a key press response, was required to reduce the effect of motor response initiation. Our results indicated the prominent involvement of the fronto-parietal and occipital cortical areas post-cue appearance, with a peculiar theta band modulation characterizing the posterior parietal cortex. Theta activity in this region was enhanced post-cue onset, decreased over time, and was enhanced again when a target appeared in an unexpected location rather than in a cued position. This suggests that the mechanism that generates IoR sequentially affects perceptual/attentional processing and motor preparation rather than response execution. Highlights: -Visually-guided isometric contraction task to check IoR effect stage was administered. -Theta and Beta Rhythmic activity on the entire cue-target interval was measured. -Fronto-parietal and occipital cortical areas involvement after cue was observed. -Posterior Parietal Theta decreased 1 s after cue and enhanced when target appeared. -IoR sequentially affects perceptual/attentional processing and motor preparation.